Interlaboratory variability of Ki67 staining in breast cancer - Focke, Cornelia M.; Bürger, Horst; van Diest, Paul J.; Finsterbusch, Kai; Gläser, Doreen; Korsching, Eberhard; Decker, Thomas; Anders, M.; Bollmann, R.; Eiting, Fr; Friedrich, K.; Habeck, J.-O.; et al. (European journal of cancer (1990), 2017)
Postanalytic issues of Ki67 assessment in breast cancers like counting method standardisation and interrater bias have been subject of various studies, but little is known about analytic variability of Ki67 staining between pathology labs. Our aim was to study interlaboratory variability of Ki67 staining in breast cancer using tissue microarrays (TMAs) and central assessment to minimise preanalytic and postanalytic influences. Thirty European pathology labs stained serial slides of a TMA set of breast cancer tissues with Ki67 according to their routine in-house protocol. The Ki67-labelling index (Ki67-LI) of 70 matched samples was centrally assessed by one observer who counted all cancer cells per sample. We then tested for differences between the labs in Ki67-LI medians by analysing variance on ranks and in proportions of tumours classified as luminal A after dichotomising oestrogen receptor–positive cancers into cancers showing low (<14%, luminal A) and high (≥14%, luminal B HER2 negative) Ki67-LI using Cochran's Q. Substantial differences between the 30 labs were indicated for median Ki67-LI (0.65%–33.0%, p < 0.0001) and proportion of cancers classified as luminal A (17%–57%, p < 0.0001). The differences remained significant when labs using the same antibody (MIB-1, SP6, or 30-9) were analysed separately or labs without prior participation in external quality assurance programs were excluded (p < 0.0001, respectively). Substantial variability in Ki67 staining of breast cancer tissue was found between 30 routine pathology labs. Clinical use of the Ki67-LI for therapeutic decisions should be considered only fully aware of lab-specific reference values. •We found substantial interlaboratory variability in Ki67 staining in breast cancer tissue.•The staining variability between labs may result in different treatment recommendations.•Prior participation in QA programs did not result in improved reproducibility among labs.•Use of uniform Ki67 cut-offs for clinical decisions is not recommended.